Effects of urbanisation on airborne pollen spectrum in cities. - Muñoz-García, Marina; De Gálvez-Montañez, Enrique; Ruiz-Mata, Rocío; Trigo-Pérez, María del Mar; Recio-Criado, María Marta; Picornell Rodríguez, Antonio (My University, 2024)
Climate change is affecting plant distribution, but human-driven land use changes are also playing a crucial role in it. Accelerated urbanisation drastically alters the landscape, generating a major impact on herbaceous plant communities in urban environments and, consequently, altering the airborne pollen concentrations in cities. Two of the most relevant impacts are vegetation removal for construction, as well as the introduction of ornamental species. The aim of this study is to analyze trends in the pollination period of herbaceous and ornamental species in the city of Malaga due to urban expansion. To do this, aerobiological data from the period 1992-2023 were used. The data were obtained by means of a Hirst-type volumetric pollen sampler installed on the roof of the Faculty of Sciences of the University of Malaga. The samples were mounted and counted following the methodology proposed by the Spanish Aerobiology Network. The main pollen season (MPS) was defined by fitting a logarithmic function to the accumulated pollen concentrations. Then, trends in the parameters of the MPS were calculated employing linear regressions. The results reveal a significant decrease in the annual pollen integral of herbaceous taxa growing in agroforestry areas such as Amaranthaceae, Plantago, and Rumex,and a significant increase in pollen from nitrophilous species such as Urtica membranacea. Olea and Platanus pollen types have also increased their presence in the atmosphere due to the expansion of olive tree crops and the growth of ornamental individuals, respectively. The expansion of urban areas causes the loss of habitats as well as the modification of plant communities, which results in a modification of the air pollen content. Therefore, urban expansion can be involved in a significant change in seasonal allergies in the urban population.
El copyright de esta publicación pertenece en exclusiva a la entidad editora, Fase 20, pero tenemos su autorización para poder subir el texto publicado al repositorio RiUMA.
Keywords: Polen - Dispersión - Efectos del clima; Aerobiology; Allergy; Pollen; Land use; Climate change